Rancang Bangun Sistem Absensi Berbasis Web pada TPQ Al Fatih - Fitri Khasanah, Cahya; Fatmasari (Jurnal Sistem Informasi, 2023)
TPQ Al Fatih is one of the non-formal educational institutions that is a place to learn the Qur’an for children to teenagers. The problems that occur in the attendance and payroll systems that have been running at this time are still recorded manually. The attendance of students is recorded in the daily attendance folder, while for teachers there is no special book to record their attendance. The calculation of teacher salaries is also still being recapitulated manually by asking directly to each teacher. The purpose of this study is to design a system that can manage attendance and perform payroll calculations using the waterfall method and UML (Unified Modeling Language) for modeling.